Imaging of the pleura. - Ayres, J; Gleeson, F (2010)
Imaging is integral to the investigation and management of pleural disease. This article addresses some of the important contributions of imaging to pleural disease, concentrating on ultrasonography, multislice computed tomography, magnetic resonance imaging, and positron-emission tomography combined with computed tomography.